Attitudes Toward and Uptake of Prenatal Genetic Screening and Testing in Twin Pregnancies. Issue 5 (10th March 2018) - Reese, Kathryn M.; Czerwinski, Jennifer; Darilek, Sandra; Johnson, Anthony; Jones, Malorie; Singletary, Claire N.
Abstract: The rate of twinning is rising and since the introduction of non‐invasive prenatal testing, interest in and uptake of genetic screening and testing in twin pregnancies has not been investigated. This study aimed to explore the attitudes toward and uptake of current prenatal genetic screening and diagnostic testing options for fetal aneuploidy in twin pregnancies. Women being seen for genetic counseling with twin gestations were recruited for participation in a descriptive study with questionnaire ( n  = 42) and semi‐structured phone interview ( n  = 15). Women were significantly more in favor of screening than diagnostic testing ( p  = 0.049). Sixty‐nine ( n  = 25) percent elected screening, while one participant had a diagnostic procedure. Women were interested in screening for preparation or reassurance despite having concerns about accuracy and uncertainty. Most women (86%) felt they would make the same decision in a singleton pregnancy. Despite this, 48% cited twin pregnancy as influential to some degree. Information learned from providers, past experiences, and family and friends were also cited as influencing and anchoring factors, suggesting that tailoring prenatal genetic counseling sessions for twins might parallel that of singletons. No significant differences between natural and assisted conception patients were found. Although it did not alter patient decisions, genetic counseling was used as a platform to raise concerns and gather information.